2017
DOI: 10.17576/akad-2017-8701-04
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Attitudes towards Biobanks in Malaysia

Abstract: The Malaysian Cabinet's approval of MyCohort in 2005 was seen as the crucial step toward the country having its very first biobank to improve the prevention, diagnosis and treatment of diseases. Past studies have shown that public attitudes towards biobanking depend heavily upon several factors including public engagement with biobanks, trust in key actors, privacy and data security, perceived benefit, altruism and certain demographic variables. The objective of this paper is to assess and compare the attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
4
11
1
Order By: Relevance
“…This finding is comparable with those of previous studies which reported that an inverse relationship exists between the perceived benefits and the perceived risks (Amin et al, 2017(Amin et al, , 2018Frewer, 2017). Hashim et al (2017) demonstrated that the intention to adopt was primarily influenced by the perceived benefits and by religious acceptance. Frewer (2017) also reported that risk and benefit perception are the key element with regard to successful new technology and product acceptance.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is comparable with those of previous studies which reported that an inverse relationship exists between the perceived benefits and the perceived risks (Amin et al, 2017(Amin et al, , 2018Frewer, 2017). Hashim et al (2017) demonstrated that the intention to adopt was primarily influenced by the perceived benefits and by religious acceptance. Frewer (2017) also reported that risk and benefit perception are the key element with regard to successful new technology and product acceptance.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in line with a study conducted by Delhove et al (2020), in which respondents with better (selfreported) knowledge were shown to have more support for both gene therapy and gene editing technologies. Moreover, several studies have also reported that the higher the education of the respondent, the more beneficial they view the technology as being, and the more supportive they are toward the application (Amin et al, 2016;Hashim et al, 2017;Wang et al, 2017). This could be due to the fact that they were actively seeking information, thus shaping a more positive view toward the application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bin Abdul Aziz and colleagues [ 5 , 28 ] have raised possible ethical and legal issues that may shape public trust (e.g., issues of data privacy and mishandling) in Malaysia. Hashim and colleagues [ 29 ] highlighted that although the majority of stakeholders in Malaysia view biobanking positively, they were also concerned about its possible risks, religious acceptance, and ownership and potential misuse issues. As described above, Malaysia is following global trends in establishing biobanks.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, Malaysia is following global trends in establishing biobanks. To reap the benefits of such technology, Hashim et al [ 29 ] recommended a further analysis of the causal factors of concerns related to biobanks. Once identified, these factors can help researchers and related governmental bodies devise appropriate educational and intervention programmes to enhance public awareness and to promote this promising technology.…”
Section: Introductionmentioning
confidence: 99%